A dynamic capabilities view of improvement capability. Issue 7 (7th November 2019) - Furnival, Joy; Boaden, Ruth; Walshe, Kieran
Abstract : Purpose: Organisations within healthcare increasingly operate in rapidly changing environments and present wide variation in performance. It can be argued that this variation is influenced by the capability of an organisation to improve: its improvement capability. However, there is little theoretical research on improvement capability. The purpose of this paper is to set out the current diverse body of research on improvement capability and develop a theoretically informed conceptual framework. Design/methodology/approach: This paper conceptualises improvement capability as a dynamic capability. This suggests that improvement capability is comprised of organisational routines that are bundled together, and adapt and react to organisational circumstances. Existing research conceptualises these bundles as three elements (microfoundations): sensing, seizing and reconfiguring. This conceptualisation is used to explore how improvement capability can be understood, by inductively categorising eight dimensions of improvement capability to develop a theoretically informed conceptual framework. Findings: This paper shows that the three microfoundations which make up a dynamic capability are present in the identified improvement capability dimensions. This theoretically based conceptual framework provides a rich explanation of how improvement capability can be configured. Originality/value: Identifying the component parts of improvement capability helps to explain why some organisations are less successful in improvement than others. This theoretically informed framework can support managers and policy makers to identify improvement capability dimensions in need of development. Further empirical research, particularly in non-market settings, such as publicly funded healthcare is required to enhance understanding of improvement capability and its configuration.